Novel heat-insulating, flame-retardant, fire-resistant and high-temperature-resistant material and application thereof

CN122897692APending Publication Date: 2026-10-13TIANJIN BENLAI TECHNOLOGY DEVELOPMENT CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611198872.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-08
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

以陶瓷纤维、二氧化硅气凝胶、硅酸铝棉为代表,具有天然的防火与耐高温特性,但力学性能较差、质地脆、易掉渣

Benefits of technology

高温结构完整性好。本发明通过热膨胀调节剂将陶瓷相、纤维、陶瓷化助剂和热膨胀调节剂四类组分的线膨胀率差异控制在±30%以内,室温至1200℃宽温域内热膨胀实现渐进匹配。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122897692A_ABST
    Figure CN122897692A_ABST
Patent Text Reader

Abstract

The application discloses a novel heat-insulating, fire-retardant, fire-resistant and high-temperature-resistant material and application thereof, and relates to the technical field of functional composite materials. The material comprises, in terms of weight parts, 20-45 parts of ceramic precursor polymer, 10-25 parts of high-temperature-resistant reinforcing fiber, 10-25 parts of ceramicization aid, 3-12 parts of thermal expansion regulator and 1-5 parts of interface compatibilizer. The ceramic precursor polymer is cracked to generate a high-temperature-resistant ceramic phase at a temperature above 600 DEG C. The thermal expansion regulator makes the linear expansion rate difference between the ceramic phase, the reinforcing fiber, the ceramicization aid and the thermal expansion regulator not more than 30% of the average value at room temperature to 1200 DEG C. The application solves the high-temperature cracking problem of the ceramicizable material through the cooperation of in-situ ceramicization and gradient thermal expansion matching, and can be applied to the fields of aerospace thermal protection and building fire prevention.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of functional composite materials technology, specifically to an organic-inorganic hybrid composite material for high-temperature thermal protection, and more particularly to a heat-insulating, flame-retardant, fire-resistant, and high-temperature resistant material that achieves high-temperature structural stability through the synergistic effect of in-situ ceramization and thermal expansion regulation. Background Technology

[0002] With the increasing safety requirements in fields such as aerospace, rail transportation, petrochemicals, building fire protection, and new energy, multifunctional materials that combine heat insulation, flame retardancy, fire resistance, and high temperature resistance have become a research hotspot.

[0003] Currently, there are three main types of this material: (a) Inorganic thermal insulation materials. Represented by ceramic fibers, silica aerogel, and aluminum silicate cotton, these materials possess natural fire-resistant and high-temperature resistant properties, but their mechanical properties are poor, they are brittle, and they are prone to crumbling. Silica aerogel powder suffers from vibration-induced shedding during use and has insufficient temperature resistance (long-term operating temperature does not exceed 650℃).

[0004] (ii) Organic thermal insulation materials. Represented by phenolic foam and polyurethane foam, they have excellent thermal insulation performance and good processability, but their flame retardant properties are insufficient, and they are easy to burn at high temperatures and release toxic fumes.

[0005] (III) Ceramizable polymer composite materials. These have seen rapid development in recent years. Chinese patent CN115651304B discloses a ceramizable ethylene-vinyl acetate copolymer / coal gangue flame-retardant and refractory composite material and its preparation method. The composite material uses ethylene-vinyl acetate copolymer as the matrix, and adds coal gangue calcined at 750–800℃, ammonium polyphosphate-coated magnesium hydroxide, zinc borate, and a char-forming and shelling agent, achieving a ceramization transformation at high temperatures to form a refractory protective layer. Chinese patent CN119286098A discloses a ceramizable polyolefin, its preparation method, and its application. Ceramization powder (a mixture of silicon dioxide, boron oxide, zinc oxide, and magnesium oxide), low-melting-point glass powder, and silicate fillers are added to the polyolefin matrix, enabling the material to form a ceramic body with a certain strength under flame conditions.

[0006] However, the aforementioned existing technologies share a common problem: during the high-temperature ceramization process, due to the significant differences in the thermal expansion coefficients of the components, thermal stress and microcracks are generated inside the material, leading to insufficient mechanical strength, structural integrity loss, and even overall failure of the ceramized product. These microcracks also become rapid diffusion channels for oxygen and heat, reducing the material's high-temperature insulation and flame-retardant effects.

[0007] The reason for the above problem is: First, the coefficient of thermal expansion of the polymer matrix is ​​typically as high as 100 × 10⁻⁶. -6 / ℃~200×10 -6 / ℃, while inorganic fillers are at 5×10 -6 / ℃~15×10 -6 The temperature difference is more than an order of magnitude. When the temperature changes drastically, interface debonding and cracking are inevitable.

[0008] Second, the ceramization process is accompanied by volume changes. Polymer thermal decomposition leads to shrinkage, and volume changes may also occur during the sintering of ceramization fillers. The inconsistency between the two generates thermal stress.

[0009] Third, existing low thermal expansion filler technology is mainly used in the field of electronic packaging (operating temperatures are usually below 200℃) to match the thermal expansion coefficient of semiconductor chips. In existing ceramizable materials, thermal expansion regulation and ceramization are independent of each other, lacking functional coupling.

[0010] Therefore, there is an urgent need to develop a new type of material that can construct a “ceramization-thermal expansion matching synergistic system”. Summary of the Invention

[0011] In order to overcome the above-mentioned defects of the prior art, the embodiments of the present invention provide a novel heat-insulating, flame-retardant, fire-resistant, and high-temperature resistant material and its application. The technical problem to be solved is to enable the ceramicizable heat-insulating and flame-retardant material to maintain structural integrity and not crack during the high-temperature ceramicization process, and to have excellent heat insulation, flame retardant and mechanical properties in a wide temperature range from room temperature to 1200℃.

[0012] Specifically, the difference in linear expansion rate of the various components within the material over a wide temperature range is controlled within an acceptable range to avoid thermal stress concentration and fundamentally eliminate the risk of cracking.

[0013] To achieve the above objectives, the present invention provides the following technical solution: The material of this invention is composed of the following components (parts by weight): 20-45 parts of ceramic precursor polymer; 10-25 parts of high-temperature resistant reinforcing fiber; 10-25 parts of ceramicizing additive; 3-12 parts of thermal expansion regulator; 1 to 5 parts of interface compatibilizer.

[0014] The above components work together to form a “ceramization-thermal expansion matching synergistic system”.

[0015] The basic solution (excluding hollow insulating microspheres and flame retardants) already achieves the core function of crack-free ceramicization. Hollow insulating microspheres and / or flame retardants are optional additional components, selectively added according to application needs to further improve thermal insulation or flame retardant performance.

[0016] Component descriptions: (1) Ceramic precursor polymer (20-45 parts) At least one of polysilazane, polycarbosilane, and polyborosilazane is selected and pyrolyzed at temperatures above 600°C to generate a high-temperature resistant ceramic phase, with a ceramization yield of not less than 60%.

[0017] Polysilazane: a colorless to pale yellow liquid with a density of approximately 1.0 g / cm³. 3 (20℃), viscosity 50mPa·s~100mPa·s, weight-average molecular weight 20000~30000. It can be thermosetting and cross-linked at 150℃~300℃, and pyrolyzed and ceramized at 800℃~1200℃, with a yield of 70%~80%. Pyrolysis process: NH3 precipitates at room temperature to 500℃, and CH4 precipitates at 500℃~700℃ under an inert atmosphere. The final product is a Si3N4 / SiC composite ceramic.

[0018] Polycarbosilane: Liquid, with a viscosity of approximately 0.25 Pa·s at room temperature. Mass loss mainly occurs between 300℃ and 700℃, and ceramization is essentially complete at 1000℃, with a yield of approximately 65%–70%, producing SiC ceramics. Platinum-containing catalysts (such as divinyltetramethyldisiloxane platinum complex) can be used at 0.1%–0.5% of the polycarbosilane mass to promote cross-linking and curing.

[0019] Polyborosilazane: The ceramicization yield is about 61% under an inert atmosphere at 1000℃. The product is mainly composed of Si3N4, BN and a small amount of SiC, and can remain amorphous above 1700℃.

[0020] The aforementioned precursor exhibits good film-forming and processability at room temperature, and decomposes into a continuous ceramic reinforcing phase at high temperature, filling the pores left by the thermal decomposition of organic components.

[0021] (2) High temperature resistant reinforcing fiber (10-25 parts) It is selected from at least one of basalt fiber, aluminum silicate fiber, alumina fiber, and mullite fiber, with a length of 3mm to 15mm and a diameter of 5μm to 20μm.

[0022] Long-term operating temperature: Basalt fiber 600℃, short-term heat resistance limit 1000℃ (heat treatment for more than 0.5 hours will degrade the fiber; pre-ceramization temperature should not exceed 900℃); Alumina fiber 1000℃; Alumina fiber 1200℃~1300℃; Mullite fiber 1300℃. Fibers shorter than 3mm have insufficient reinforcement, while those longer than 15mm are prone to entanglement and agglomeration; diameters less than 5μm are costly, while diameters greater than 20μm weaken interfacial bonding.

[0023] Basalt fiber: softening point not lower than 960℃, coefficient of thermal expansion approximately 6×10⁻⁶ -6 / ℃~8×10-6 / ℃ (20℃~600℃).

[0024] Aluminosilicate fiber: Zirconium-containing type can withstand long-term operating temperatures above 1300℃, with a coefficient of thermal expansion of approximately 4×10⁻⁶. -6 / ℃~6×10 -6 / ℃ (20℃~1000℃).

[0025] Alumina fiber: Short-term thermal expansion coefficient at 1400℃ is approximately 7×10⁻⁶. -6 / ℃~9×10 -6 / ℃ (20℃~1200℃).

[0026] Mullite fiber: coefficient of thermal expansion approximately 5×10 -6 / ℃~6×10 -6 / ℃ (20℃~1300℃).

[0027] The fibers form a three-dimensional random network skeleton, which bears the mechanical load at room temperature and serves as a ceramic structure support at high temperature.

[0028] (3) Ceramicizing additives (10-25 parts) It is selected from at least one of kaolin, mullite powder, silica powder, and zirconium oxide powder, with a particle size of 0.5 μm to 10 μm. Particles smaller than 0.5 μm are prone to agglomeration, while those larger than 10 μm have insufficient reactivity.

[0029] Kaolin (Al2O3·2SiO2·2H2O): It dehydrates at 500℃~700℃ to become metakaolin, and decomposes at 900℃~1000℃ to form mullite and cristobalite, forming a refractory ceramic phase.

[0030] Mullite powder (3Al2O3·2SiO2): melting point about 1850℃, good chemical stability.

[0031] Silica powder (SiO2): Submicron size, large specific surface area, and high reactivity.

[0032] Zirconia powder (ZrO2): melting point about 2700℃, contains 3 mol% Y2O3 stabilizer to suppress the volume expansion of the monoclinic phase to the tetragonal phase at high temperature.

[0033] This component undergoes a solid-phase reaction with the precursor pyrolysis products at high temperatures, promoting ceramization and improving density and strength.

[0034] (4) Thermal expansion regulator (3-12 parts) The particles are selected from at least one of spodumene, aluminum titanate, and cordierite, with a particle size of 1 μm to 20 μm. Particles smaller than 1 μm are costly to disperse, while particles larger than 20 μm are difficult to adjust uniformly.

[0035] The linear expansion rate difference among the four components—ceramic phase, reinforcing fiber, ceramicizing aid, and thermal expansion regulator—formed by the modifier after the ceramic precursor is decomposed at room temperature to 1200°C does not exceed ±30% of the average linear expansion rate of the four components.

[0036] Among them, "linear expansion rate" is the ratio of the change in length during the heating process to the original length; "linear expansion rate difference" is the difference between the maximum and minimum linear expansion rates of the four components at the same temperature; "average linear expansion rate" is the arithmetic mean of the four. "±30%" means that the percentage of the difference value relative to the average value does not exceed 30%. Adding less than 3 parts is insufficient for adjustment, and more than 12 parts will damage the continuity of the polymer matrix.

[0037] Spodumene (Li₂O·Al₂O₃·4SiO₂): Monoclinic crystal system, with three polymorphs: α-, β-, and γ-. The α-to-β polymorph undergoes an irreversible unidirectional transformation at 930℃~1000℃. β-Spodumene is a high-temperature stable polymorph with near-zero or even negative thermal expansion; its coefficient of thermal expansion is -0.03×10⁻⁶ at 100℃~1000℃. -6 / ℃~4.08×10 -6 / ℃, melting point 1423℃. It melts into a liquid phase at high temperatures and acts as a binder during cooling to promote the densification of ceramic sintering.

[0038] Aluminum titanate (Al₂TiO₅): Melting point 1860℃, orthorhombic crystal system, coefficient of thermal expansion 0.5×10⁻⁶ from room temperature to 1200℃. -6 / ℃~1.5×10 -6 It has a low thermal conductivity of 1W / (m·K) to 2W / (m·K) at ℃, can work for a long time at 1400℃, and is resistant to thermal shock.

[0039] Cordierite (2MgO·2Al2O3·5SiO2): Melting point 1460℃, coefficient of thermal expansion 1.5×10 from room temperature to 800℃. -6 / ℃~2.0×10 -6 It exhibits stable chemical properties and excellent thermal shock resistance at / ℃.

[0040] By selecting the type and amount of the above-mentioned regulators, the thermal expansion behavior of the composite material from room temperature to 1200℃ can be precisely controlled to achieve gradual matching and eliminate the hidden danger of thermal stress cracking.

[0041] The "matching" mentioned in this invention means that the difference in linear expansion rate relative to the average linear expansion rate does not exceed ±30%, at which point the thermal stress is lower than the strength limit of each component.

[0042] (5) Interface compatibilizer (1-5 parts) At least one of γ-aminopropyltriethoxysilane (KH550), γ-glycidyl etheroxypropyltrimethoxysilane (KH560), or titanate coupling agent is used to modify the surface of inorganic fillers to form an organic functional group grafted layer.

[0043] Before use, silane coupling agents are hydrolyzed in an acidic ethanol solution with a pH of 4–5 and then mixed with inorganic fillers for reaction; titanate coupling agents do not require hydrolysis and can be mixed directly.

[0044] The ethoxy group (-OEt) of KH550 reacts with the hydroxyl group (-OH) on the surface of the inorganic filler to form a chemical bond, while the amino group (-NH2) forms a hydrogen bond or reacts with the organic matrix, forming a "molecular bridge" at the interface, reducing interfacial tension and enhancing bonding strength. Adding less than 1 part has no significant effect, while adding more than 5 parts increases cost and may form an independent phase.

[0045] (6) Optional component: hollow heat insulation microspheres (8-20 parts) To further improve thermal insulation performance and reduce density, it can be selectively added. It is selected from at least one of hollow ceramic microspheres, hollow glass microspheres, and cenospheres, with a particle size of 10μm to 200μm, preferably 10μm to 100μm.

[0046] Hollow ceramic microspheres: closed-cell spherical shape, filled with inert gas (N2 or CO2), true density 0.4 g / cm³ 3 ~0.8g / cm 3 Thermal conductivity ≤0.1W / (m·K), compressive strength ≥10MPa (ASTM D3102).

[0047] Hollow glass microspheres: True density 0.2 g / cm³ 3 ~0.5g / cm 3 Thermal conductivity ≤0.05W / (m·K), compressive strength 3MPa~10MPa.

[0048] Cenospheres: Hollow ceramic microspheres derived from fly ash, with a melting point ≥1400℃, compressive strength up to 350MPa or more, and low cost.

[0049] The hollow cavity of the hollow microspheres acts as a physical buffer space at high temperatures, absorbing the peak value of instantaneous thermal shock stress.

[0050] (7) Optional component: flame retardant (5-15 parts) To further enhance flame retardant properties, it can be selectively added. It may contain at least one ingredient selected from ammonium polyphosphate, expandable graphite, and aluminum hydroxide.

[0051] Expandable graphite: initial expansion temperature 150℃~200℃, expansion ratio 200~400 times. After being heated and expanded, it forms a worm-like porous carbon layer, which acts as a heat insulation and oxygen barrier.

[0052] Ammonium polyphosphate ((NH4PO3)n): contains about 31% to 32% phosphorus, decomposes at ≥250℃, decomposes to produce polyphosphoric acid, catalyzes carbonization and releases non-flammable gases such as NH3.

[0053] Aluminum hydroxide (Al(OH)3): Decomposes at approximately 220℃, breaking down into Al2O3 and water. The water vapor absorbs heat and dilutes the flammable gas.

[0054] This flame retardant system is halogen-free and environmentally friendly. The flame retardant expands or decomposes at 150℃–400℃ to absorb heat and form an initial protective layer; above 600℃, it initiates ceramization to form a dense ceramic refractory layer, creating a temperature gradient relay protection. Adding less than 5 parts results in insufficient effectiveness, while adding more than 15 parts negatively impacts mechanical and thermal insulation properties.

[0055] The inventiveness of this invention lies in the synergy between "in-situ ceramization" and "gradient thermal expansion matching": Synergistic effect 1: Thermal expansion regulators ensure crack-free ceramization. The ceramization process is accompanied by mass loss (approximately 30%–35% weight loss in polycarbosilane) and volume shrinkage, while the polymer matrix undergoes thermal expansion of approximately 100 × 10⁻⁶. -6 / ℃~200×10 -6 / ℃, fiber size approximately 4×10 -6 / ℃~9×10 -6 / ℃, approximately 5×10⁻⁶ ceramization additives -6 / ℃~8×10 -6 / ℃, the difference generates thermal stress. Thermal expansion regulators, through the negative expansion of β-spodumene and the low expansion characteristics of aluminum titanate or cordierite, adjust the overall coefficient of thermal expansion to be in harmony with each component.

[0056] Synergistic effect two: Ceramization products contribute to structural integrity. With the thermal expansion regulator ensuring no cracking, the in-situ generated ceramic phase reacts with fibers and ceramization additives to form a continuous three-dimensional inorganic network, filling thermal decomposition pores and maintaining or even improving high-temperature mechanical properties.

[0057] Synergistic effect three: The physical buffering of hollow microspheres and the chemical regulation of thermal expansion regulators form a guarantee.

[0058] The technical effects and advantages of this invention are as follows: The structure exhibits good high-temperature integrity. This invention controls the difference in linear expansion rates of the four components—ceramic phase, fiber, ceramicizing aid, and thermal expansion regulator—within ±30% through a thermal expansion regulator, achieving progressive matching of thermal expansion over a wide temperature range from room temperature to 1200℃.

[0059] Stable mechanical properties at high temperatures. In-situ ceramization forms a continuous ceramic reinforcing phase. After treatment at 1000℃, the compressive strength retention rate is not less than 103%. Moreover, the degree of ceramization deepens with increasing temperature, and the continuous network of ceramic phase becomes more complete, exhibiting the anomalous reinforcement characteristic of "the higher the temperature, the more stable the strength", which breaks through the law of mechanical property decay of traditional composite materials at high temperatures.

[0060] It exhibits excellent thermal insulation properties. The hollow cavities of the microspheres endow the material with a low thermal conductivity, which can be reduced to 0.038 W / (m·K) after addition. Simultaneously, the hollow cavities of the microspheres act as a physical buffer space at high temperatures, absorbing instantaneous thermal shock stress. Together with the chemical regulation of the thermal expansion regulator, this forms a dual-layer thermal stress release mechanism of "physical buffering + chemical regulation," achieving triple protection in conjunction with the ceramization process.

[0061] It exhibits excellent flame retardant properties. The flame retardant and ceramization form a temperature gradient relay protection: the flame retardant decomposes and absorbs heat at 150℃~400℃ to form an initial protective layer, and ceramization initiates above 600℃ to form a dense fire-resistant layer. The limiting oxygen index can reach over 45%, meeting the GB 8624 Class A non-combustible requirement, and its flame retardant level is significantly better than traditional organic thermal insulation materials.

[0062] Lightweight and heat-resistant. The basic design has a bulk density of no more than 0.6 g / cm³. 3 The concentration of the substance decreased to 0.42 g / cm³ after the addition of hollow microspheres. 3 It has a long-term operating temperature of no less than 1200℃ and can withstand flame impact of more than 1400℃ in the short term. It is suitable for harsh high-temperature scenarios such as aerospace thermal protection and building fire protection.

[0063] The raw materials are readily available, the process is simple, and the application range is wide. All components are industrially mature raw materials, and the preparation involves only conventional mixing, molding, and curing operations, requiring no special equipment and facilitating large-scale production. Examples 1-5 show consistent performance trends under different formulation compositions, indicating that the technical solution of this invention has universality and robustness. Attached Figure Description

[0064] Figure 1 This is a schematic diagram of the microstructure of the material of the present invention at room temperature; Figure 2 This is a schematic diagram of the microstructure of the material of the present invention after high-temperature ceramization; Figure 3 The curves show a comparison of the thermal expansion behavior of the material of this invention and existing ceramicizable composite materials after high-temperature treatment. Figure 4 This is a comparison chart of the compressive strength of the material of this invention and existing ceramicizable composite materials after high-temperature treatment. Detailed Implementation

[0065] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0066] As attached Figures 1 to 4 The present invention relates to a novel heat-insulating, flame-retardant, fire-resistant, and high-temperature resistant material and its application, the specific implementation details of which are as follows: To facilitate understanding of this invention, the following terms are defined: "Ceramicization yield": the percentage of the mass of the residual solids after high-temperature pyrolysis of the precursor relative to the original mass.

[0067] "Linear expansion rate": The ratio of the change in length during the heating process to the original length.

[0068] "Difference in linear expansion rate": The difference between the maximum and minimum values ​​of the linear expansion rate of the four components (ceramic phase, fiber, additives, and regulators) at the same temperature.

[0069] "Average linear expansion rate": the arithmetic mean of the linear expansion rates of the four components.

[0070] "Long-term service temperature": The highest temperature at which a material maintains its basic properties without significant deterioration under continuous heating conditions (specifically for fibers in this invention).

[0071] "Ceramicization-thermal expansion matching synergistic system": a functional system composed of precursors and regulators, in which the ceramicization reaction and thermal expansion match synchronously and cooperate with each other during the heating process.

[0072] "Ceramicization" and "inorganization" are synonymous. "Floating beads" is a subcategory of "hollow ceramic microspheres". "Expandable graphite" refers to unexpanded raw materials, while "expanded graphite" is the product after thermal expansion.

[0073] "Interfacial compatibilizer" and "coupling agent" are synonymous. Throughout the text, "parts" refers to "parts by weight". Temperature is measured in "°C", and pressure in "MPa". The unit for the coefficient of thermal expansion, " / °C", is equivalent to " / K" and will be used consistently throughout the text.

[0074] (I) Preparation method Step 1: Raw material drying pretreatment.

[0075] Place the thermal expansion regulator, ceramicizing agent, and flame retardant (if selected) separately in a forced-air drying oven and dry at 100℃~120℃ for 2~4 hours to make the powder moisture content ≤0.5% (mass fraction).

[0076] Step 2: Interface modification.

[0077] Dissolve the interface compatibilizer in anhydrous ethanol to prepare a 2%–5% (w / w) solution (stir at room temperature until completely dissolved). Adjust the pH of the silane coupling agent to 4–5 with dilute acetic acid to promote hydrolysis; no pH adjustment is required for the titanate coupling agent.

[0078] The dried powder is added to the solution (powder-to-liquid mass ratio 1:2 to 1:5), and stirred in a water bath at 60℃ to 80℃ for 1 to 3 hours at a speed of 200 to 500 r / min. After filtration, it is vacuum dried at 80℃ to 100℃ for 2 to 4 hours to obtain the surface-modified powder.

[0079] Step 3: Mix.

[0080] Place the ceramic precursor polymer in a mixing container, add the surface-modified powder at room temperature, and stir at 100 rpm to 300 rpm for 10 to 20 minutes. Add hollow heat-insulating microspheres (if selected) and high-temperature resistant reinforcing fibers (microspheres added first), and stir at 50 rpm to 150 rpm for 20 to 40 minutes to obtain the mixture.

[0081] Step 4: Shaping.

[0082] The mixture is injected into a mold preheated to 40℃~60℃, pressed at 5MPa~15MPa, and held at pressure for 5~15 minutes. For hollow glass microspheres (compressive strength 3MPa~10MPa), the pressure is controlled at 5MPa~10MPa; for hollow ceramic microspheres (≥10MPa) or cenospheres (≥350MPa), the pressure can be increased to 10MPa~15MPa.

[0083] Step 5: Curing and cross-linking.

[0084] The molded material, along with the mold, is placed in a curing oven and cured under an inert atmosphere (N2 or Ar, purity ≥99.9%) at a temperature of 150℃~300℃ for 2~5 hours. It is then cooled to room temperature in the oven (rate ≤3℃ / min) and demolded.

[0085] Curing temperature: for polysilazane, 200℃~250℃ / 3 hours is preferred; for polycarbosilane (containing platinum catalyst), 180℃~220℃ / 3 hours is preferred, and for polycarbosilane without catalyst, 250℃~300℃ / 3~5 hours is preferred (the amount of catalyst is 0.1%~0.5% of the mass of polycarbosilane); for polyborosilazane, 200℃~280℃ / 3~4 hours is preferred.

[0086] Step 6: Optional post-treatment (high-temperature pre-ceramization).

[0087] The cured preform is heat-treated at 600℃~1200℃ for 0.5~3 hours. When using basalt fiber, the pre-ceramization temperature should not exceed 900℃ (1000℃ is the instantaneous tolerance temperature; heat treatment for more than 0.5 hours will degrade the fiber); when using aluminosilicate or alumina fiber, the temperature can be increased to 1000℃~1200℃.

[0088] (II) Implementation Examples Example 1 (Basic Formula): 30 parts of polysilazane (MW25000, 75mPa·s / 20℃), 18 parts of basalt fiber (6mm / 10μm), 18 parts of kaolin powder (3μm), 6 parts of spodumene powder (10μm, α-crystal form), and 3 parts of KH550.

[0089] Preparation: Spodumene powder and kaolin powder were dried at 110℃ for 3 hours. A 3% ethanol solution of KH550 was prepared (3g KH550 per 100mL ethanol), and the pH was adjusted to approximately 4.5 with dilute acetic acid. The powder was added (powder-to-liquid ratio 1:3), and the mixture was stirred in a water bath at 70℃ for 2 hours (300r / min). After filtration, the mixture was vacuum dried at 90℃ for 3 hours. Polysilazane and the modified powder were stirred at 200r / min at 25℃ for 15 minutes, and basalt fibers were added and stirred at 100r / min for 30 minutes. The mixture was poured into a steel mold at 50℃ and held at 10MPa for 10 minutes. High-purity N2 was passed through a tube furnace (200mL / min), and the temperature was increased to 200℃ at a rate of 2℃ / min and held for 3 hours. The mixture was then cooled to room temperature at a rate of 2℃ / min for demolding.

[0090] Example 2 (Higher Temperature Resistance): 25 parts of polycarbosilane (0.25 Pa·s / 25℃, containing 0.3% platinum catalyst), 20 parts of aluminum silicate fiber (containing zirconium type, 10 mm / 8 μm), 22 parts of mullite powder (5 μm), 5 parts of aluminum titanate powder (15 μm), and 2 parts of titanate coupling agent (NDZ-101).

[0091] The preparation method is the same as in Example 1, except that the curing temperature is 220°C and the curing time is 3 hours.

[0092] Example 3 (balancing thermal insulation and mechanical properties): 28 parts of polyborosilazane, 15 parts of alumina fiber (8mm / 12μm), 15 parts of zirconium oxide powder (2μm, containing 3mol% Y2O3), 7 parts of cordierite powder (12μm), and 4 parts of KH560.

[0093] The preparation method is the same as in Example 1, except that the curing temperature is 250°C and the curing time is 4 hours.

[0094] Example 4 (containing hollow microspheres): 28 parts of polysilazane, 16 parts of basalt fiber (6mm), 16 parts of kaolin powder (3μm), 5 parts of spodumene powder (10μm), 3 parts of KH550, and 14 parts of hollow ceramic microspheres (50μm).

[0095] The preparation method is the same as in Example 1, except that in step three, microbeads are added first and then fibers are added, and the molding pressure is 8 MPa.

[0096] Example 5 (containing flame retardant): 24 parts of polycarbosilane (containing 0.3% platinum catalyst), 18 parts of aluminum silicate fiber (10mm), 20 parts of mullite powder (5μm), 5 parts of aluminum titanate powder (15μm), 2 parts of titanate coupling agent, and 10 parts of expandable graphite (expansion ratio 300 times).

[0097] The preparation method is the same as in Example 1, except that in step one, the expandable graphite is dried together (temperature ≤120℃) and cured at 220℃ for 3 hours.

[0098] (III) Comparative Example Comparative Example 1 (without thermal expansion regulator): 30 parts polysilazane, 18 parts basalt fiber, 18 parts kaolin powder, and 3 parts KH550. Preparation method is the same as in Example 1. Used to verify the necessity of a thermal expansion regulator.

[0099] Comparative Example 2 (Replacement with Conventional Low Thermal Expansion Packing): 30 parts polysilazane, 18 parts basalt fiber, 18 parts kaolin powder, 6 parts fused silica powder (10 μm), and 3 parts KH550. Preparation method is the same as in Example 1. The coefficient of thermal expansion of the fused silica powder is approximately 0.5 × 10⁻⁶. -6 / ℃, but no crystal transformation occurs at high temperatures (spodumene undergoes an α→β transformation at 930℃~1000℃, resulting in negative expansion). This is used to verify the specific selectivity of the thermal expansion regulator of this invention.

[0100] Comparative Example 3 (without interfacial compatibilizer): 30 parts polysilazane, 18 parts basalt fiber, 18 parts kaolin powder, and 6 parts spodumene powder were prepared. After drying each powder at 110℃ for 3 hours, they were directly mixed with polysilazane at room temperature and stirred for 30 minutes. The mixture was then pressed into shape at 10 MPa and cured at 200℃ under N2 atmosphere for 3 hours. This was used to verify the role of the interface compatibilizer.

[0101] (iv) Performance testing methods Thermal conductivity: GB / T10294-2008 or ASTMC518-21, sample size 300mm×300mm×(10~50)mm, test temperature 25℃, 500℃, 800℃.

[0102] Compressive strength: GB / T8813-2020 or ASTM D1621-16, specimen size 50mm×50mm×50mm, loading rate 2mm / min. Compressive strength was tested at room temperature and after a 1000℃×2-hour high-temperature treatment, with an average value of ≥5 specimens per group. Retention rate = (High-temperature strength / Room temperature strength) × 100%.

[0103] Coefficient of thermal expansion: GB / T4339-2008 or ASTME228-22, sample size 5mm×5mm×50mm, temperature range 25℃~1200℃, heating rate 3℃ / min.

[0104] Thermal shock resistance: The sample is 50mm×50mm×25mm. After being kept at 1100℃ for 30 minutes, it is immersed in 25℃ water for 5 minutes to cool. Cracks are observed under a 10× stereomicroscope. The number of cycles is recorded until cracks appear.

[0105] Limiting oxygen index: GB / T2406.2-2009, sample size 100mm×10mm×4mm, ≥15 samples per group.

[0106] Bulk density: GB / T6343-2009, sample size 50mm×50mm×50mm.

[0107] Linear expansion rate difference: TMA tested the linear expansion rates of four components (ceramic phase, fiber, additives, and regulators) from room temperature to 1200℃, calculated the difference between the maximum and minimum values ​​at each temperature point and the arithmetic mean, and verified whether the difference was ≤ ±30% of the average value. Refer to ASTM E831-19.

[0108] (v) Performance test results Table 1 Performance test results of Examples 1-5 and Comparative Examples 1-3

[0109] (1) Comparative Example 1 (without thermal expansion regulator) had a compressive strength retention rate of only 48.6%, a thermal shock resistance of only 8 cycles, and a linear expansion rate difference of 47.6%, which far exceeded ±30%, proving the necessity of thermal expansion regulator.

[0110] (2) Comparative Example 2 (fused silica powder substitute) retains 66.9% of compressive strength and has a thermal shock resistance of 15 cycles. The difference in linear expansion rate is 38.2%, which is still more than ±30%, proving that not any low thermal expansion filler can achieve the effect of the present invention. The present invention is creative in its selection of regulator types.

[0111] (3) The room temperature compressive strength of Comparative Example 3 (without interface compatibilizer) was 12.3 MPa, which was significantly lower than that of Example 1 (18.6 MPa). The thermal shock resistance of 25 cycles was lower than that of Example 1 (36 cycles), which proves that the interface compatibilizer plays an important role in room temperature mechanical properties and long-term stability.

[0112] (4) The difference in linear expansion rate of Examples 1-5 is 22.8% to 26.1% and is ≤ ±30%. The thermal shock resistance is ≥33 times, the high temperature compressive strength retention rate is ≥103%, and the thermal conductivity is ≤0.048W / (m·K), which proves the universality and robustness of the technical solution.

[0113] (5) In Example 4 (hollow microspheres), the thermal conductivity decreased to 0.038 W / (m·K), and the density decreased to 0.42 g / cm³. 3 The thermal insulation and lightweighting effects are significantly improved. Example 5 (expandable graphite) has an LOI of 46.5%, meeting the Class A non-flammability requirement, and the addition of flame retardants does not affect the core synergistic mechanism.

[0114] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A novel heat-insulating, flame-retardant, fire-resistant, and high-temperature-resistant material, characterized in that, Based on parts by weight, it includes the following components: 20-45 parts of ceramic precursor polymer; 10-25 parts of high-temperature resistant reinforcing fiber; 10-25 parts of ceramicizing additive; 3-12 parts of thermal expansion regulator; 1-5 parts of interface compatibilizer; The ceramic precursor polymer is selected from at least one of polysilazane, polycarbosilane, and polyborosilazane. The ceramic precursor polymer undergoes pyrolysis and ceramization at a temperature above 600°C to generate a high-temperature resistant ceramic phase. The ceramization yield of the ceramic precursor polymer is not less than 60%. The long-term service temperature of the high-temperature resistant reinforcing fiber is not lower than 600℃; The particle size of the ceramicizing agent is 0.5 μm to 10 μm; The thermal expansion regulator is selected from at least one of spodumene, aluminum titanate, and cordierite, with a particle size of 1μm to 20μm. The thermal expansion regulator ensures that the difference in linear expansion rate among the ceramic phase formed after the pyrolysis of the ceramic precursor polymer, the high-temperature resistant reinforcing fiber, the ceramicizing agent, and the thermal expansion regulator in the material does not exceed ±30% of the average linear expansion rate of the four components within a temperature range from room temperature to 1200℃. The interface compatibilizer is used to modify the surface of inorganic fillers, forming an organic functional group grafted layer on the surface of the inorganic fillers.

2. The novel heat-insulating, flame-retardant, fire-resistant, and high-temperature-resistant material according to claim 1, characterized in that, The high-temperature resistant reinforcing fiber is selected from at least one of basalt fiber, aluminum silicate fiber, alumina fiber, and mullite fiber, with a fiber length of 3mm to 15mm and a fiber diameter of 5μm to 20μm; the surface of the high-temperature resistant reinforcing fiber is pretreated with a coupling agent, which is selected from silane coupling agents or titanate coupling agents.

3. The novel heat-insulating, flame-retardant, fire-resistant, and high-temperature-resistant material according to claim 1, characterized in that, The ceramicizing agent is selected from at least one of kaolin, mullite powder, silica powder, and zirconium oxide powder; wherein the kaolin decomposes to form a mullite refractory phase in the temperature range of 900℃ to 1000℃, and the zirconium oxide powder contains 3 mol% Y2O3 as a stabilizer.

4. The novel heat-insulating, flame-retardant, fire-resistant, and high-temperature-resistant material according to claim 1, characterized in that, The interface compatibilizer is selected from at least one of γ-aminopropyltriethoxysilane, γ-glycidoxypropyltrimethoxysilane, or titanate coupling agent. When the interface compatibilizer is a silane coupling agent, it is pre-hydrolyzed in an acidic ethanol solution with a pH of 4-5 before use, and then mixed and reacted with the inorganic filler. When the interface compatibilizer is a titanate coupling agent, it does not need to be pre-hydrolyzed and can be directly mixed with the inorganic filler.

5. The novel heat-insulating, flame-retardant, fire-resistant, and high-temperature-resistant material according to claim 1, characterized in that, The thermal expansion regulator is spodumene, which transforms from α-crystalline to β-crystalline in the temperature range of 930℃ to 1000℃. The coefficient of thermal expansion of the β-crystalline spodumene is -0.03×10⁻⁶ in the temperature range of 100℃ to 1000℃. -6 / ℃~4.08×10 -6 / ℃.

6. The novel heat-insulating, flame-retardant, fire-resistant, and high-temperature resistant material according to claim 1, characterized in that, The thermal expansion regulator is aluminum titanate, which has a melting point of 1860℃ and a coefficient of thermal expansion of 0.5×10⁻⁶ in the temperature range of room temperature to 1200℃. -6 / ℃~1.5×10 -6 / ℃.

7. The novel heat-insulating, flame-retardant, fire-resistant, and high-temperature-resistant material according to claim 1, characterized in that, The thermal expansion regulator is cordierite, which has a melting point of 1460℃ and a coefficient of thermal expansion of 1.5 × 10⁻⁶ over a temperature range from room temperature to 800℃. -6 / ℃~2.0×10 -6 / ℃.

8. The novel heat-insulating, flame-retardant, fire-resistant, and high-temperature-resistant material according to claim 1, characterized in that, The material also includes 8 to 20 parts by weight of hollow thermal insulation microspheres, wherein the hollow thermal insulation microspheres are selected from at least one of hollow ceramic microspheres, hollow glass microspheres, and cenospheres, and have a particle size of 10 μm to 200 μm. The hollow ceramic microspheres have a thermal conductivity of not more than 0.1 W / (m·K) and a compressive strength of not less than 10 MPa.

9. The novel heat-insulating, flame-retardant, fire-resistant, and high-temperature-resistant material according to claim 1, characterized in that, The product also includes 5 to 15 parts by weight of flame retardant, wherein the flame retardant is selected from at least one of ammonium polyphosphate, expandable graphite, and aluminum hydroxide; wherein the expandable graphite has an initial expansion temperature of 150°C to 200°C and an expansion ratio of 200 to 400 times.

10. The application of the novel heat-insulating, flame-retardant, fire-resistant, and high-temperature resistant material according to any one of claims 1 to 9 in the preparation of aerospace thermal protection components, building fireproof components, thermal insulation layers for high-temperature pipelines in petrochemical industries, and / or thermal protection layers for new energy battery packs.

Citation Information

Patent Citations

  • A ceramicizable ethylene vinyl acetate copolymer / coal gangue flame-retardant and refractory composite material and its preparation method

    CN115651304B

  • Ceramic polyolefin as well as preparation method and application thereof

    CN119286098A